Tropical Coastal Wetlands Ameliorate Nitrogen Export During Floods - Adame, Maria Fernanda; Roberts, Melanie E.; Hamilton, David P.; Ndehedehe, Christopher E.; Reis, Vanessa; Lu, Jing; Griffiths, Matthew; Curwen, Graeme; Ronan, Mike (Frontiers in Marine Science, 2019)
Wetlands can increase resilience to extreme climatic events and have a key role in protection and water quality improvement in coastal ecosystems. Studies in tropical coastal wetlands at a catchment scale are scarce, and most work has been undertaken on small, temperate wetlands. In this study, we tested whether natural coastal wetlands in a tropical catchment (Tully-Murray, Queensland, Australia) could ameliorate nitrogen (N) exported to the Great Barrier Reef during a flood event. We measured denitrification rates in different types of coastal wetlands (mangroves, saltmarshes, waterbodies with macrophytes, and floodplain wetlands dominated by Melaleuca spp.) to assess their potential contribution to N losses during the 6-day duration of a flood in March 2018. Denitrification potential was variable across the landscape, and we identified “hotspots” in sub-catchments with high NO3--N concentrations (0.4 - 0.6 mg L-1) and large areas of wetlands (> 800 ha, > 40% of the sub-catchment). These hotspots can denitrify up to 10 t of NO3--N per day during a flood. We used our measured denitrification rates to provide input parameters for a model that includes the main biogeochemical processes affecting N transformations within wetlands (nitrification, denitrification, plant uptake, sedimentation, anammox, and mineralisation), and accounts for transport via the duration, depth, and flow of water. Model simulations of a sub-catchment of the Tully-Murray indicate that flood inundation of large areas of natural wetlands (> 40% of the sub-catchment area) could potentially remove 70% of the incoming NO3--N load in the first 24 h of the flood. The management and restoration of coastal tropical wetlands could play a critical role in sustaining the health of coastal ecosystems through water quality improvement.